Motavizumab for prophylaxis of respiratory syncytial virus in high-risk children: a noninferiority trial - Carbonell-Estrany, Xavier; Simões, Eric A F; Dagan, Ron; Hall, Caroline B; Harris, Brian; Hultquist, Micki; Connor, Edward M; Losonsky, Genevieve A (Pediatrics (Evanston), 2010)
Palivizumab reduces respiratory syncytial virus (RSV) hospitalization in children at high risk by approximately 50% compared with placebo. We compared the efficacy and safety of motavizumab, an investigational monoclonal antibody with enhanced anti-RSV activity in preclinical studies, with palivizumab. This randomized, double-blind, multinational, phase 3, noninferiority trial assessed safety and RSV hospitalization in 6635 preterm infants aged <or=6 months at enrollment or children aged <or=24 months with chronic lung disease of prematurity who received 15 mg/kg palivizumab or motavizumab monthly. Secondary end points included outpatient medically attended lower respiratory tract infections (MALRIs), RSV-specific LRIs, otitis media, antibiotic use, development of antimotavizumab antibodies, and motavizumab serum concentrations. Motavizumab recipients had a 26% relative reduction in RSV hospitalization compared with palivizumab recipients, achieving noninferiority. Motavizumab was superior to palivizumab for reduction of RSV-specific outpatient MALRIs (50% relative reduction). Overall, adverse events (AEs) were not significantly different between groups. Cutaneous events were reported in 2 percentage points more motavizumab recipients (7.2% vs 5.1%); most were mild, but 0.3% resulted in dosing discontinuation. Antidrug antibodies (ADA) were detected in 1.8% of motavizumab recipients. Patients with anti-drug antibody reported 6 RSV events and 17 cutaneous events. Children receiving prophylaxis with motavizumab or palivizumab had low rates of RSV hospitalization; motavizumab recipients experienced 50% fewer RSV MALRIs than palivizumab recipients. AEs were similar in both groups, although cutaneous AEs were higher for motavizumab recipients. Motavizumab may offer an improved alternative in prophylaxis for serious RSV disease in infants and children at high risk.